With All Thy Mind: Worship That Honors the Way God Made Us - Glick, Robert P. (Rowman & Littlefield Publishers, 2006)
The worship terrain has changed, but a consensus has yet to emerge even about what worship is, let alone how we should worship. Increasingly, however, people are hungry not just to know about God, but to experience God with all they they are—mind, heart, body, and soul. Worship must engage all of the senses. Recalling the biblical and early church's witness regarding worship and denominational worship traditions, Robert Glick examines the place of words, songs, sacraments, and symbols in worship—in light of what we now know about the complexities of the human brain. He also examines roadblocks to more balanced worship and identifies the characteristics of a “well-tempered worship service.” Glick expresses how our understanding of the wonders of our God-given brains can lead us to worship that is fuller, richer, and more truthful, and thus more receptive to the Spirit.